Credit, currency or deratives instruments of global financial stability or crisis? - Choi, Jongmoo Jay, 1945-; Papaioannou, Michael (Emerald, 2009)
This edited volume on Credit, Currency, or Derivatives: Instruments of Global Financial Stability or Crisis contains original papers that examine various issues concerning the role, the structure and functioning of credit, currency and derivatives instruments and markets as they relate to financial crises. We stress the importance of the inter-linkages of these instruments and markets in promoting or hindering financial stability or crises as well as government policies, on a local and global level. The papers in this volume highlight various aspects of credit and currency instruments and markets, along with their interactions, for the stability of domestic and international financial systems. Particular emphasis is given on the failures of regulatory systems and their implications for systemic financial crises. Also, the papers analyze the costs of financial crises and explore the institutional and economic arrangements that could ameliorate the adverse effects of financial crises in advanced and emerging-market countries.
Keywords: Business cycles.; Financial crises.; Monetary policy.; elektronické knihy; electronic books